A cell-free microtiter plate screen for improved [FeFe] hydrogenases. - James A Stapleton (Public Library of Science (PLoS), 2010)
Background [FeFe] hydrogenase enzymes catalyze the production and dissociation of H(2), a potential renewable fuel. Attempts to exploit these catalysts in engineered systems have been hindered by the biotechnologically inconvenient properties of the natural enzymes, including their extreme oxygen sensitivity. Directed evolution has been used to improve the characteristics of a range of natural catalysts, but has been largely unsuccessful for [FeFe] hydrogenases because of a lack of convenient screening platforms. Methodology/principal findings Here we describe an in vitro screening technology for oxygen-tolerant and highly active [FeFe] hydrogenases. Despite the complexity of the protocol, we demonstrate a level of reproducibility that allows moderately improved mutants to be isolated. We have used the platform to identify a mutant of the Chlamydomonas reinhardtii [FeFe] hydrogenase HydA1 with a specific activity approximately 4 times that of the wild-type enzyme. Conclusions/significance Our results demonstrate the feasibility of using the screen presented here for large-scale efforts to identify improved biocatalysts for energy applications. The system is based on our ability to activate these complex enzymes in E. coli cell extracts, which allows unhindered access to the protein maturation and assay environment.